Psychometric Properties of the Sarson Exam Anxiety Scale (Field Study on a Sample of Damascus University Students) (Journal of Hama University, 2022)
The current research aims to study the psychometric properties of the Sarson Exam Anxiety Scale in the Syrian environment, by using various methods to study the validity and reliability of the scale, and by applying the scale to a sample of Damascus University students, and the sample consisted of (380) students from the Faculties of Education and Economics. It included (136) male and (244) female students. And the Sarson exam anxiety scale was used, which consists of (38) items distributed within three dimensions (cognitive, behavioral, and physical). The results showed that the Sarson exam anxiety scale has good psychometric properties in the Syrian environment, and is suitable for using it within the limits of the research sample. This is done by verifying its validity indicators using several methods, which are (content validity, criterion validity, and structural validity). As well as checking the indicators of reliability using several methods, which are (repetition reliability, the internal consistency reliability using the Cronbach alpha coefficient).
Keywords: Psychometric Properties; Validity; Reliability; Exam Anxiety